THE INFLUENCE OF ENTREPRENEURIAL PRACTICES AND THE USE OF SOCIAL MEDIA ON THE ENTREPRENEURIAL INTEREST OF GRADE XI STUDENTS AT SMK NEGERI 5 DENPASAR FOR THE 2022/2023 ACADEMIC YEAR - Ni Kadek Darmara Padma Nirmala; Putu Diah Asrida; Ni Luh Putu Cahayani (Arthaniti Studies, 2023)
This study aims to determine the effect of entrepreneurial practices and the use of social media on interest in entrepreneurship at SMK Negeri 5 Denpasar for the academic year 2022/2023. This study uses a quantitative approach ex post fact through the method of observation, interviews, documentation, and questionnaires in data collection. The number of respondents in this study were 219 students. The results of this study indicate that (1)There is a partial effect of Entrepreneurial Practices on Interest in Entrepreneurship as evidenced by the results of the ttest 16,626 > ttable 2,26 with a significan value of 0.000 < 0.05; (2)There is a partial effect of the use of social media on interest in entrepreneurship as evidenced by the results of the ttest 21,000 > ttable 2.26 with a significan value of 0.000 < 0.05; (3)There is a simultaneous influence on Entrepreneurial Practices and the Use of Social Media on Entrepreneurial Interests seen from the results of the Ftest > Ftable of 272.918 > 3.04 with a significan value of 0.000 < 0.05. The result of the coefficient of determination shows the magnitude of the value Adjusted R square is 0.714, which means 71.4% variations in Entrepreneurial Interest are influenced by Entrepreneurship Practices and Use of SocialMedia, while the remaining 28.6% influenced by other factors that are not included in the variables of this study.